(untitled) (Modern American Journal of Social Sciences and Humanities, 2025)
Can human-centricity of EU AI act be standardized across borders? This question sits at the intersection of legal harmonization, technological fluidity, and ethical imperative, defining the scope and viability of the European regulatory experiment in global digital governance. The quest for standardization reflects a complex policy ambition to assert normative influence while managing intrinsic technological uncertainty. Achieving cross-border uniformity necessitates a framework adaptable to varying socio-political contexts and technological interpretations.